Cadmium induces changes in sucrose partitioning, invertase activities, and membrane functionality in roots of Rangpur Lime (Citrus limonia L. Osbeck) - Podazza, Griselda (2006)
Cadmium (Cd) uptake effects on sucrose content, invertase activities, and plasma membrane functionality were investigated in Rangpur lime roots (Citrus limonia L. Osbeck). Cadmium accumulation was significant in roots but not in shoots and leaves. Cadmium produced significant reduction in roots DW and increment in WC. Leaves and shoots did not show significant differences on both parameters. Sucrose content was higher in control roots than in Cd-exposed ones. Apoplastic sucrose content was much higher in Cd-exposed roots than in control ones. Cd-exposed roots showed a significant decrease in both cell wall-bound and cytoplasmic (neutral) invertase activities; while the vacuolar isoform did not show any change. Alterations in lipid composition and membrane fluidity of Cd-exposed roots were also observed. In Cd-exposed roots phospholipid and glycolipid contents decreased about 50%, while sterols content was reduced about 22%. Proton extrusion was inhibited by Cd. Lipid peroxidation and proton extrusion inhibition were also detected by histochemical analysis. This work findings demonstrate that Cd affects sucrose partitioning and invertase activities in apoplastic and symplastic regions in Rangpur lime roots as well as the plasma membrane functionality and H+-ATPase activity.